2015
DOI: 10.1016/j.toxlet.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine promotes α-tubulin deacetylation in endothelial cells: The protective role of acetyl-l-carnitine

Abstract: Methamphetamine (METH) is a powerful psychostimulant drug used worldwide for its reinforcing properties. In addition to the classic long-lasting monoaminergic-disrupting effects extensively described in the literature, METH has been consistently reported to increase blood brain barrier (BBB) permeability, both in vivo and in vitro, as a result of tight junction and cytoskeleton disarrangement. Microtubules play a critical role in cell stability, which relies on post-translational modifications such as a-tubuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The primary event of neurodegeneration that is caused by METH has been direct impairment of the BBB prior to mediation of the central nervous system (CNS) damage (Banks and Ericson, 2010). BBB impairment by METH has been reviewed in several mechanisms, including the hyperactivity of NADPH oxidase (NOX)-2 which generates excessive amounts of free radicals, such as reactive oxygen species (ROS) and reactive nitrogen species (RNS) (Ramirez et al, 2009;Park et al, 2012); the dysfunction of cytoskeleton and the trans-membrane protein of tight junction, which is the controlling of paracellular permeability (Park et al, 2013;Fernandes et al, 2015); the dysfunction of the uptake and the efflux activities (ElAli et al, 2012); and the activation of caspase cascade in cell death response or apoptosis (Abdul-Muneer et al, 2011;Ma et al, 2014;Fisehr et al, 2015). Moreover, overexpression of inflammatory mediators such as inducible nitric oxide synthase (iNOS), nitric oxide (NO), interleukin (IL)-1, and tumor necrosis factor (TNF), which is an important factor in inflammatory response, has also been reported (Fernandes et al, 2014;CoelhoSantos et al, 2015;Parikh et al, 2015;Zhang et al, 2015;Skaper et al, 2014;Husain et al, 2015;Kothur et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The primary event of neurodegeneration that is caused by METH has been direct impairment of the BBB prior to mediation of the central nervous system (CNS) damage (Banks and Ericson, 2010). BBB impairment by METH has been reviewed in several mechanisms, including the hyperactivity of NADPH oxidase (NOX)-2 which generates excessive amounts of free radicals, such as reactive oxygen species (ROS) and reactive nitrogen species (RNS) (Ramirez et al, 2009;Park et al, 2012); the dysfunction of cytoskeleton and the trans-membrane protein of tight junction, which is the controlling of paracellular permeability (Park et al, 2013;Fernandes et al, 2015); the dysfunction of the uptake and the efflux activities (ElAli et al, 2012); and the activation of caspase cascade in cell death response or apoptosis (Abdul-Muneer et al, 2011;Ma et al, 2014;Fisehr et al, 2015). Moreover, overexpression of inflammatory mediators such as inducible nitric oxide synthase (iNOS), nitric oxide (NO), interleukin (IL)-1, and tumor necrosis factor (TNF), which is an important factor in inflammatory response, has also been reported (Fernandes et al, 2014;CoelhoSantos et al, 2015;Parikh et al, 2015;Zhang et al, 2015;Skaper et al, 2014;Husain et al, 2015;Kothur et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…BBB impairment by METH has been reviewed in several mechanisms, including the hyperactivity of NADPH oxidase (NOX)-2 which generates excessive amounts of free radicals, such as reactive oxygen species (ROS) and reactive nitrogen species (RNS) (Ramirez et al, 2009;Park et al, 2012); the dysfunction of cytoskeleton and the transmembrane protein of tight junction, which is the controlling of paracellular permeability (Park et al, 2013;Fernandes et al, 2015); the dysfunction of the uptake and the efflux activities (Elali et al, 2012); and the activation of caspase cascade in cell death response or apoptosis (Abdul et al, 2011;Ma et al, 2014;Fisher et al, 2015). Moreover, overexpression of inflammatory mediators such as inducible nitric oxide synthase (iNOS), nitric oxide (NO), interleukin (IL)-1, and tumor necrosis factor (TNF) α, which is an important factor in inflammatory response, has also been reported (Fernandes et al, 2014;Coelho-Santos et al, 2015;Parikh et al, 2015;Zhang et al, 2015;Skaper et al, 2014;Hussain et al, 2015;Kothur et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with recent findings in endothelial cells (Fernandes et al . ), we found that METH exposure led to the loss of AcetTUB, which is highly enriched in stable MTs. The loss of AcetTUB was more pronounced in TH‐positive striatal axons than in striatal tissue lysates (Fig.…”
Section: Discussionmentioning
confidence: 54%